Immune responses to an inactivated Johne’s disease vaccine in cattle - CHAITANYA, R K; REDDY, Y KRISHNA MOHAN; THANGAVELU, A (The Indian Journal of Animal Sciences, 2022)
The objective of this study was to develop a vaccine against Johne’s disease for calves and study its immune efficacy. A heat inactivated Johne’s disease vaccine in mineral oil adjuvant was developed using the strain predominant in Tamil Nadu and tested for its efficacy in calves for a period of 8 months by ELISA for antibodies and by Interferon-γ ELISA, MTT assay and flow cytometry for cell mediated immune responses. Vaccinated calves had high levels of seroconversion as compared to control calves from second month post vaccination (PV) and antibodies persisted throughout the study period. Lymphoproliferative response specific to MAP antigen and increase in the IFN-γ levels was observed in the vaccinated calves from 30 days PV and the response was significantly higher in vaccinated calves compared to control group up to four months PV. In flow cytometry analysis, the peak percentages of CD4+ and CD8+ T cells were noticed at three months PV among vaccinated animals. Overall, our results suggested that the inactivated Johne’s disease vaccine was effective in stimulating the immune system of the calves with significant MAP specific responses.